(3TQM GdhQbGJ aj CUhd Gdabgs - (3ceGd GdOjf Hf GeGe GdcGedjIs; (3CHj GdeYGdj YHO Gdedc Hf YHO Gddg Hf jhSa GdLhjfj, EeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3CeG gPG JYdjb Ydi GdhQbGJ GdefShHI dTjN GdGSdGe GdHMQ GdQHGfi YHO Gdedc GeGe GdMQejf s
(3BNQgG (B:s
(3GdOdjd Cf GdfHi Udi Gddg Ydjg hSde NWC GdeLJgO JGQI , hUhHg CNQi s
(3GdfSNI HgG MhGTs
(3ai Chdg agQS HGdehVhYGJ GdhGQOg ai GdcJGH cJHg GdcJGH Hbde bdjd GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160s
Keywords: (3eJaQbGJs